The Mitochondrial Respiratory Chain Maintains the Photosynthetic Electron Flow in Arabidopsis thaliana Leaves under High-Light Stress. (11th October 2019) - Yamada, Shoya; Ozaki, Hiroshi; Noguchi, Ko
Abstract: The plant respiratory chain includes the ATP-coupling cytochrome pathway (CP) and ATP-uncoupling alternative oxidase (AOX). Under high-light (HL) conditions, plants experience photoinhibition, leading to a damaged photosystem II (PSII). The respiratory chain is considered to affect PSII maintenance and photosynthetic electron transport under HL conditions. However, the underlying details remain unclear. In this study, we investigated the respiratory chain functions related to PSII maintenance and photosynthetic electron transport in plants exposed to HL stress. We measured the HL-induced decrease in the maximum quantum yield of PSII in the leaves of wild-type and AOX1a -knockout ( aox1a ) Arabidopsis thaliana plants in which CP was partially inhibited by a complex-III inhibitor. We also calculated PSII photodamage and repair rate constants. Both rate constants changed when CP was partially inhibited in aox1a plants, suggesting that the respiratory chain is related to both processes. Before HL stress, photosynthetic linear electron flow (LEF) decreased when CP was partially inhibited. After HL stress, aox1a in the presence of the CP inhibitor showed significantly decreased rates of LEF. The electron flow downstream from PSII and on the donor side of photosystem I may have been suppressed. The function of respiratory chain is required to maintain the optimal LEF as well as PSII maintenance especially under the HL stress.